The Women Empowerment in Tanjung Rejo Village through Honey Bee Cultivation on Mangrove Forest Area - Cicilia Kimberly Oldy Saragih; Joice Margaretha Zebua; Nadya Nurhaliza; Hairani Siregar (TALENTA Publisher, 2025)
Honey bee cultivation in mangrove forests has the potential to increase the income of local communities and support ecosystem sustainability. The results of honey production are not only processed and marketed, but also contribute to improving the household economy in tanjung rejo village. In addition, honey bees also have an important role in the process of pollinating plants that support the sustainability of mangrove plant ecosystems. However, this business also has challenges both risks from predators to the health of honey bees. This study uses a qualitative method with a case study approach to understand in depth the process of women's empowerment in honey bee cultivation and the resulting economic impactHoney bee cultivation in mangrove forests has the potential to increase the income of local communities and support ecosystem sustainability. The results of honey production are not only processed and marketed, but also contribute to improving the household economy in tanjung rejo village. In addition, honey bees also have an important role in the process of pollinating plants that support the sustainability of mangrove plant ecosystems. However, this business also has challenges both risks from predators to the health of honey bees. This study uses a qualitative method with a case study approach to understand in depth the process of women's empowerment in honey bee cultivation and the resulting economic impact